Sustainable Development Goals Program in Primary Schools in the ASEAN Region: A Bibliometric and Systematic Review 2014-2024 - Irawan, Nico; Hadi Wibowo, Amiruddin; Handika, Ilham (EduStream: Jurnal Pendidikan Dasar, 2024)
Sustainable Development (SDGs) has become a popular topic in many studies which prove how important the movement is to the nation's growth. The aim of this research is to explore popular research trends, especially on SDGs programs related to ASEAN elementary schools from 2014-2024. This research design is a bibliometric research method. This method is used to study the most significant topics and determine the quantity of SDGs publication trends. The results of this research show that research that has increased significantly is regarding sustainable education which reflects that basic education does not only focus on literacy and numeracy but also achieves desires, social justice, and students resulting in the achievement of SDG 4. Analysis of the themes found that the majority of research focus on inclusive education, social welfare, and economic outlook among ASEAN countries. The conclusion of this research is that the increase in research regarding SDGs in elementary schools has increased, there is a need for regional cooperation to distribute best practices to instill SDGs values ​​into the basic education curriculum so that fair, inclusive and sustainable education can be achieved.